1996
DOI: 10.1097/00006123-199601000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Microdialysis of Glutamate and Aspartate Two Vascular Territories after Aneurysmal Subarachnoid Hemorrhage

Abstract: Cerebral ischemia associated with subarachnoid hemorrhage may have severe consequences for neuronal functioning. The excitatory amino acid neurotransmitters glutamate and aspartate have been shown to be of particular importance for ischemia and ischemic neuronal damage. For seven patients who underwent early surgery for ruptured intracranial aneurysms, intracerebral microdialysis of glutamate and aspartate was performed to monitor local metabolic changes in the medial temporal (all seven patients) and subfront… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 22 publications
2
34
0
6
Order By: Relevance
“…The neurotoxic effects of widespread subarachnoid blood associated with transient cerebral ischemia cause diffuse cortical damage that occurs immediately after the hemorrhage (Doczi, 1985;Doczi et al 1986;Enblad et al, 1996;Gotoh et al, 1984;Hutchinson et al, 2000;Jackowski et al, 1990;Nilsson et al, 1996Nilsson et al, , 1999Persson et al, 1996;Sarrafzadeh et al, 1998Sarrafzadeh et al, , 2002Saveland et al, 1996;Schulz et al, 2000;Staub et al, 2000;Untemberg et al, 2001). This damage results from the interaction of numerous pathophysiologic factors where presumably, the blood itself and/or active substances derived in part from the degradation of the extravasated blood are centrally involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The neurotoxic effects of widespread subarachnoid blood associated with transient cerebral ischemia cause diffuse cortical damage that occurs immediately after the hemorrhage (Doczi, 1985;Doczi et al 1986;Enblad et al, 1996;Gotoh et al, 1984;Hutchinson et al, 2000;Jackowski et al, 1990;Nilsson et al, 1996Nilsson et al, , 1999Persson et al, 1996;Sarrafzadeh et al, 1998Sarrafzadeh et al, , 2002Saveland et al, 1996;Schulz et al, 2000;Staub et al, 2000;Untemberg et al, 2001). This damage results from the interaction of numerous pathophysiologic factors where presumably, the blood itself and/or active substances derived in part from the degradation of the extravasated blood are centrally involved.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, bedside intracerebral microdialysis monitoring of patients with SAH exhibiting signs of delayed ischemia revealed dramatic changes in extracellular concentrations of excitatory amino acids, including glucose, piruvate, lactate, glycerol, and glutamate, confirming that these characteristic metabolic changes occur during vasospasm (Unterberg et al, 2001;Zouh et al, 1996). Moreover, a correlation between EAA concentrations and patient clinical status has been demonstrated Hutchinson et al, 2000;Inage et al, 2000;Nilsson et al, 1996Nilsson et al, , 1999Persson et al, 1996;Sarrafzadeh et al, 1998Sarrafzadeh et al, , 2002Saveland et al, 1996;Schulz et al, 2000;Staub et al, 2000).…”
Section: Introduction Dmentioning
confidence: 95%
See 1 more Smart Citation
“…However, there is no evidence that 1 method is more efficient and reliable than other methods. [37][38][39] Cumulative meta-analysis, including 1981 patients altogether, demonstrated that the frequency of shunt-dependent hydrocephalus was not significantly different between coiling and clipping. This result differs with the prior meta-analysis conducted in 2007, 40 which showed that the risk of shuntdependent hydrocephalus was significantly higher after coiling than clipping for ruptured intracranial aneurysms.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…1 This approach was adopted to validate MD with the ultimate goal, which was to obtain a reliable monitoring instrument in neurosurgical intensive care. [2][3][4][5][6][7][8] The reliability of the interstitial substances as markers of ischemia, eg, the lactate/pyruvate (LP) ratio and glutamate, was substantiated when the ischemic state of the brain could be directly assessed by PET in the MD probe regions and compared with biochemical changes of the microdialysates sampled simultaneously. 1 To study focal ischemia followed by reperfusion under more standardized conditions, an experimental middle cerebral artery (MCA) occlusion (MCAO) model of transient focal ischemia with reperfusion was established in primates.…”
mentioning
confidence: 99%